Investigation into the Influence of Parallel Offset Wear on Stirling Engine Piston Rod Oil-Free Lubrication Seal - Wenhan Cao; Zhou Chang; Ao Zhou; Xuqiang Dou; Gui Gao; Jun Gong (Machines, 2022)
The oil-free lubrication seal of a piston rod plays an important role in the application of a Stirling engine. Parallel offset in a piston rod ruins the symmetry of the seal and affects the sealing performance when the seal is worn. In this paper, based on a motion analysis and the finite element method, a three-dimensional model of the Cap-seal was established, and its performance was numerically and experimentally investigated. The results show that parallel offset of the piston rod increases the possibility of seal damage and has no obvious effect on leakage. Under high pressures and low pre-compression ratios, the Cap-seal shows a good sealing capability and exhibits a higher propensity for mechanical damage. A good agreement was obtained between the numerical and experimental results. This study offers guidelines regarding the design and application of oil-free lubrication seals for a Stirling piston rod.